VAGINAL DELIVERY OF MUMMIFIED FETUS IN A CROSSBRED COW - KHASATIYA, C T; GANGURDE, H B; CHAUHAN, G G (The Indian Journal of Animal Reproduction, 2011)
A case of fetal mummification probably developed at 5-6 months of gestation that was successfully delivered per vaginum following use of prostaglandin, corticosteroid and valethemate bromide in a primiparous HF crossbred cow is put on record.